2005
DOI: 10.1111/j.1360-0443.2005.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic effects of alcohol cues on sexual attraction

Abstract: Aims The present study tested whether suboptimal priming (which may be defined as 'under viewing conditions rendering conscious identification highly improbable') with alcohol-related stimuli would activate existing expectancies about alcohol's effects on sexual desire. It was predicted that alcohol cues, relative to non-alcohol cues, would activate expectancies of alcohol's aphrodisiac properties. We hypothesized that for men, stronger expectancies in this regard would predict an increased tendency to judge w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 54 publications
(42 reference statements)
8
58
0
1
Order By: Relevance
“…For instance, it has been shown that sexual attractiveness increases after exposure to alcohol-related cues (Friedman, McCarty, Förster, & Denzler, 2005). This, too, might happen automatically.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For instance, it has been shown that sexual attractiveness increases after exposure to alcohol-related cues (Friedman, McCarty, Förster, & Denzler, 2005). This, too, might happen automatically.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Thus alcohol may increase sexual desire via a dopaminergic mechanism, accounting for the first part of Shakespeare's famous observation that alcohol "provokes desire but takes away the performance." On the other hand, mere exposure to alcohol-related cues has also been reported to increase attractiveness ratings, particularly in those who believe that alcohol stimulates sexual desire (Friedman, McCarthy, Forster & Denzler, 2005). As alcohol intoxication is The present study investigated the relationship between BAC and facial attractiveness ratings by heterosexual university student social drinkers of both genders in naturalistic settings (campus pub and campus parties).…”
mentioning
confidence: 94%
“…Resulting behavior may be shaped more by these expectancies than the actual physical effects of the ingested alcohol. As reported by Friedman, McCarthy, Forster, and Denzler (2005) in an experimental study of male college students, higher alcohol expectancies of increased sex drive when such individuals are exposed to alcohol-related cues may be enough (even without consumption) to produce "beer goggles" (i.e., judging others more attractive than would normally be the case), and thus potentially affect actual sexual risks. Our ability in this study to make inferences about the role of expectations in the risky behaviors of adolescents is limited; however, this dimension was not a focus of the larger research study and thus not measured.…”
Section: Limitationsmentioning
confidence: 86%